Sustainable Business Development of Village Enterprises: Pembangunan Bisnis Berkelanjutan untuk Usaha Desa - Salsabilla, Fadya; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Village-Owned Enterprises (BUMDes) contribute to rural economic transformation through entrepreneurship and innovation. Specific Background: BUMDes development often faces obstacles such as limited managerial competence and weak strategic planning. Knowledge Gap: Few studies explore comprehensive development models that align business innovation with local potential. Aims: This study aims to examine development strategies implemented by BUMDes in enhancing local economic welfare. Results: The findings reveal that effective business unit diversification, market linkage expansion, and digital marketing increase BUMDes competitiveness and community income. Novelty: The study proposes a participatory business model emphasizing collaboration between government, youth, and local entrepreneurs. Implications: Policy strengthening, digital adaptation, and community participation are essential to achieve sustainable BUMDes growth. Highlights: Diversified units enhance BUMDes competitiveness. Digital tools expand rural business reach. Collaboration accelerates local economic resilience.